2013
DOI: 10.1177/0300060513490618
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib induces apoptosis and autophagy in osteosarcoma cells through mitogen-activated protein kinase pathway in vitro

Abstract: This study provided new insights into the mechanisms underlying bortezomib-induced apoptosis in human osteosarcoma HOS cells, and suggests that bortezomib could be a potent chemotherapeutic agent in the treatment of osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…4A) reduced the level of soluble PARK2. It has been recently shown that bortezomib treatment leads to activation of autophagy (32,33); hence, we conclude from these data that mutant PARK2 C289G may be primarily degraded through autophagy under such conditions. However, bortezomib treatment significantly (albeit not completely) reduced the protective effects of HSPB1 and HSPB4 on PARK2 C289G aggregation, while having only a modest effect on HSPB7-mediated protection and no effect on HSPB2-mediated protection (Fig.…”
Section: Hspb1supporting
confidence: 53%
“…4A) reduced the level of soluble PARK2. It has been recently shown that bortezomib treatment leads to activation of autophagy (32,33); hence, we conclude from these data that mutant PARK2 C289G may be primarily degraded through autophagy under such conditions. However, bortezomib treatment significantly (albeit not completely) reduced the protective effects of HSPB1 and HSPB4 on PARK2 C289G aggregation, while having only a modest effect on HSPB7-mediated protection and no effect on HSPB2-mediated protection (Fig.…”
Section: Hspb1supporting
confidence: 53%
“…Recent experimental and clinical data have shown that proteasome inhibitors serve as a new and promising class of anticancer agents [21,24,77,79,84,87,144]. However, the data presented in this review proved beyond doubt that proteasome inhibition induces www.fhc.viamedica.pl autophagy in the majority of cells.…”
Section: Final Remarksmentioning
confidence: 76%
“…According to Ding et al [75], JNK but not XBP-1 seems to be involved in the induction of autophagy after treatment with proteasome inhibitors. In a subsequent study these authors observed that increased autophagy in HOS cells in response to bortezomib corresponded with altered levels of intracellular mitogen-activated protein kinase (MAPK) signalling molecules such as decreased levels of phosphorylated MAPK kinase (MEK1/2) and extracellular signal-regulated kinase (ERK1/2), and simultaneous increase of phosphorylated JNK and p38 MAPK [77]. Also, after exposure of melanoma cells to bortezomib, no changes were observed in the total expression levels of IRE1, ASK1, JNK and p38, however, this proteasome inhibitor triggered the phosphorylation of these proteins [24].…”
Section: Unfolded Protein Responsementioning
confidence: 96%
See 2 more Smart Citations